Dynamic Inputs and Resource (Mis)Allocation. - Asker, John; Collard-Wexler, Allan; De Loecker, Jan (Journal of Political Economy, 2014)
We investigate the role of dynamic production inputs and their associated adjustment costs in shaping the dispersion of static measures of capital misallocation within industries (and countries). Across nine data sets spanning 40 countries, we find that industries exhibiting greater time-series volatility of productivity have greater cross-sectional dispersion of the marginal revenue product of capital. We use a standard investment model with adjustment costs to show that variation in the volatility of productivity across these industries and economies can explain a large share (80-90 percent) of the cross-industry (and cross-country) variation in the dispersion of the marginal revenue product of capital.